Electrical reduction of perovskite electrodes for accelerating exsolution of nanoparticles. (20th May 2019) - Chanthanumataporn, Merika; Hui, Jianing; Yue, Xiangling; Kakinuma, Katsuyoshi; Irvine, John T.S.; Hanamura, Katsunori
Abstract: Growth of finely dispersed nanocatalysts by exsolution of metal nanoparticles from perovskite oxides under reducing conditions at elevated temperature is a promising approach of producing highly active catalytic materials. An alternative method of exsolution using an applied potential has been recently shown to potentially accelerate the exsolution process of nanoparticles that can be achieved in minutes rather than the hours required in chemical reduction. In the present study, we investigate exsolution of nanoparticles from perovskite oxides of La0.43 Ca0.37 Ni0.06 Ti0.94 O3-γ (LCTNi) and La0.43 Ca0.37 Ni0.03 Fe0.03 Ti0.94 O3-γ (LCTNi-Fe) under applied potentials in carbon dioxide atmosphere. The impedance spectra of single cells measured before and after electrochemical poling at varying voltages showed that the onset of exsolution process occurred at 2 V of potential reduction. An average particle size of the exsolved nanoparticles observed after testing using a scanning electron microscopy was about 30–100 nm. The cells with the reduced electrodes exhibited desirable electrochemical performances not only in pure carbon dioxide (current density of 0.37 A cm −2 for LCTNi and 0.48 A cm −2 for LCTNi-Fe at 1.5 V) but also in dry hydrogen (0.36 W cm −2 for LCTNi and 0.43 W cm −2 for LCTNi-Fe).